Soccer boots elevate plantar pressures in elite male soccer professionals - Carl, H. D.; Pauser, J.; Swoboda, B.; Jendrissek, A.; Brem, M. (Clinical Journal of Sport Medicine, 2014)
Objective: The present study measured the difference in peak plantar pressure between running shoes and soccer shoes in male soccer professionals [mean (SD): age, 23 (4) years; height, 184 (7) cm; weight, 81 (6) kg].